Pemikiran Abdullah Saeed tentang Riddah dan Hak Asasi Manusia - Tasmuji, Tasmuji (Religió: Jurnal Studi Agama-agama, 2011)
As an intellectual Muslim, Abdullah Saeed obviously concerns to contemporary issues of Islam. He attempts to contextualize Islamic values based on faith that Islamic doctrine is shâlih li kulli zamân wa makân. This attempt appears, for instance, on his views relating to the concept of riddah (apostasy) and human rights. Saeed offers what he names as progressive-ijtihadits methodology: a method to re-interpret religious texts based on necessities of contemporary people. Bids progressive-ijtihadist methodology is still facing many obstacles, but should be used as an alternative and a way out. The biggest challenge is the internal constraints, such as unpreparedness of Muslims themselves for the brave dissent, the pleasure of the culture of blaming each other (takfîr), and a cynical view of some groups of Muslims who consider this method as a deviation from the original Islamic teachings. Saeed uses historical analysis to observe and set the concept of riddah as a sin not as crime. By using historical analysis, he said, we can examine the concept due to scientific approach: centripetal and centrifugal. Therefore, the concept of riddah consists of both ontological and existential problems.